The Implementation of Merdeka Curriculum to Realize Indonesia Golden Generation: A Systematic Literature Review - Syahrir Syahrir; Pujiriyanto Pujiriyanto; Musdalifa Musdalifa; Sakinah Fitri (AL-ISHLAH: Jurnal Pendidikan, 2024)
The Merdeka Curriculum serves as a pivotal framework for cultivating a resilient and socially adept golden generation, aligning with the cherished principles of Pancasila. This study endeavors to evaluate the efficacy of the Merdeka Curriculum in fostering Indonesia's golden generation, gauging its influence on soft skills and character development as per the Pancasila learner profile, and identifying obstacles encountered during its implementation across diverse educational settings in Indonesia. Employing a systematic literature review approach following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, this research sourced pertinent articles from the "Semantic Scholar and Google Scholar" platforms, yielding 20 articles meeting the criteria spanning from 2022 to 2023. Findings reveal that the Merdeka Curriculum's implementation holds immense promise in nurturing Indonesia's golden generation, facilitating the cultivation of 21st-century skills, granting educators autonomy in pedagogical design, and leveraging digital media. Its holistic approach fosters an educational milieu emphasizing students' character and social competencies grounded in Pancasila values. Despite encountered challenges, educational institutions are emerging as hubs of innovation and catalysts for positive transformation. Nevertheless, delving deeper into the specific components and enduring impacts of the Merdeka Curriculum is imperative. Recommendations for future research entail comprehensive examinations of participation across various educational tiers and geographic regions, alongside longitudinal studies to elucidate its sustained effects.